Neanderthals in the desert? Population history best explains Middle Palaeolithic technological heterogeneity in Arabia - James Blinkhorn; Huw S. Groucutt; W. Christopher Carleton; Eric Andrieux; Simon J. Armitage; Ceri Shipton; Paul S. Breeze; Nick Drake; Abdulaziz Al-Omari; Faisal Al-Jibreen; Abdullah M. Alsharekh; Eleanor M.L. Scerri; et al. (Quaternary Science Reviews, 2026)

Not by chemistry alone: Tephrostratigraphy, correlation, and context at two Palaeolithic sites in the southern Caucasus and Armenian Highlands - D.S. Adler; V.L. Cullen; K.N. Wilkinson; B. Gasparyan; N. Tushabramishvili; P. Griffith; C. Mallol; J.P. Gill; T.Z. Kovach; S. Blockley; P. Glauberman; V.C. Smith (Quaternary Science Reviews, 2025)

Wind regime changes in the Euro-Atlantic region driven by Late-Holocene Grand Solar Minima - P. Harding; C. Martin-Puertas; J. Sjolte; A. A. Walsh; R. Tjallingii; C. Langdon; S. P. E. Blockley; A. Brauer; P. Langdon; A. M. Milner; R. Muscheler; M. Perez (Climate Dynamics, 2023)

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

The lateglacial Quercus expansion in the southern European Alps: rapid vegetation response to a late Allerød climate warming? - W. Finsinger; C. S. Lane; G. J. van Den Brand; F. Wagner‐Cremer; S. P. E. Blockley; A. F. Lotter (Journal of Quaternary Science, 2011)
A pollen‐inferred vegetation shift, from pioneer birch–pine woodland to mixed pine–summergreen oak forests, in the southern Alpine forelands, is commonly attributed to a centennial‐scale warming that occurred between the Gerzensee Oscillation (GO) and the Younger Dryas. Two microtephra layers bracketing the Younger Dryas onset (the Laacher See Tephra and the Vedde Ash) improve the chronology at Lago Piccolo di Avigliana (northern Italy) and allowed accurate correlation with Central European records where the GO is clearly detected. We used pollen percentages, pollen accumulation rates (PARs) and plant macrofossils to assess the population dynamics of Quercus , and leaf‐cuticle analysis for a better taxonomic identification of Quercus . Our results indicate that the species that was locally present was probably Quercus robur . PARs suggest that the population expansion started as early as the Bølling and followed an exponential increase through time. We attribute this gradual shift to increasing summer temperatures and longer growing seasons which contrast with a gradually decreasing temperature trend as recorded in Greenland ice cores and in Central Europe. Breaks or set‐backs in the PAR record may indicate the biotic response to minor Lateglacial cooling events of different life‐history stages in the Quercus population. Copyright © 2011 John Wiley & Sons, Ltd.

The chronology of abrupt climate change and Late Upper Palaeolithic human adaptation in Europe - S. P. E. Blockley; S. M. Blockley; R. E. Donahue; C. S. Lane; J. J. Lowe; A. M. Pollard (Journal of Quaternary Science, 2006)
This paper addresses the possible connections between the onset of human expansion in Europe following the Last Glacial Maximum, and the timing of abrupt climate warming at the onset of the Lateglacial (Bölling/Allerød) Interstadial. There are opposing views as to whether or not human populations and activities were directly ‘forced’ by climate change, based on different comparisons between archaeological and environmental data. We review the geochronological assumptions and approaches on which data comparisons have been attempted in the past, and argue that the uncertainties presently associated with age models based on calibrated radiocarbon dates preclude robust testing of the competing models, particularly when comparing the data to non‐radiocarbon‐based timescales such as the Greenland ice core records. The paper concludes with some suggestions as to the steps that will be necessary if more robust tests of the models are to be developed in the future. Copyright © 2006 John Wiley & Sons, Ltd.

Bayesian analysis of radiocarbon chronologies: examples from the European Late‐glacial - S. P. E. Blockley; J. J. Lowe; M. J. C. Walker; A. Asioli; F. Trincardi; G. R. Coope; R. E. Donahue (Journal of Quaternary Science, 2004)
Although there are many Late‐glacial (ca. 15 000–11 000 cal. yr BP) proxy climate records from northwest Europe, some analysed at a very high temporal resolution (decadal to century scale), attempts to establish time‐stratigraphical correlations between sequences are constrained by problems of radiocarbon dating. In an attempt to overcome some of these difficulties, we have used a Bayesian approach to the analysis of radiocarbon chronologies for two Late‐glacial sites in the British Isles and one in the Adriatic Sea. The palaeoclimatic records from the three sites were then compared with that from the GRIP Greenland ice‐core. Although there are some apparent differences in the timing of climatic events during the early part of the Late‐glacial (pre‐14 000 cal. yr BP), the results suggest that regional climatic changes appear to have been broadly comparable between Greenland, the British Isles and the Adriatic during the major part of the Late‐glacial (i.e. between 14 000 and 11 000 cal. yr BP). The advantage of using the Bayesian approach is that it provides a means of testing the reliability of Late‐glacial radiocarbon chronologies that is independent of regional chronostratigraphical (climatostratigraphical) frameworks. It also uses the full radiocarbon inventory available for each sequence and makes explicit any data selection applied. Potentially, therefore, it offers a more ‘objective’ basis for comparing regional radiocarbon chronologies than the conventional approaches that have been used hitherto. Copyright © 2004 John Wiley & Sons, Ltd.

Chemical alteration of tephra in the depositional environment: theoretical stability modelling - A. M. Pollard; S. P. E. Blockley; K. R. Ward (Journal of Quaternary Science, 2003)
The study of the chemical stability of vitreous material in aqueous media is well‐established. There has to date been little consideration of the implications of variations in the chemical durability of tephra in Quaternary tephrochronology. Chemical alteration can take the form of cationic leaching from the matrix, or complete destruction of the silica network, either of which could constrain the ability to chemically identify distal tephra. Here we apply established models of vitreous durability to the published chemical analyses of a large number of Icelandic tephras in order to predict their relative durabilities under equivalent conditions. This suggests that some important tephras have relatively poor chemical stability, and that rhyolitic tephras are, in general, more stable than basaltic. We conclude that tephras should be expected to show predictable differential chemical stability in the post‐depositional environment. Copyright © 2003 John Wiley & Sons, Ltd.